Pengaruh Faktor Abiotik terhadap Produksi Protease dari Isolat Bakteri M1-23 - Mira Rosnawita; Anthoni Agustien; Nasril Nasir (Jurnal Biologi Universitas Andalas, 2015)
A study on the influence of abiotic factors in producing protease by bacterial isolates M1-23 was conducted from May 2013 to December 2013 in the  Laboratory of Microbiology, Department of  Biology, Andalas University, Padang. This study aimed to find optimal conditions by isolate M1-23 to produce protease. This study consists of two stages. First stage used to produce the best protease and the second used to increase enzim homogenity. The result showed that the highest enzyme activity was  at medium temperature 550 C and pH 7.5. The best homogenity was produced at 125 rpm of agitation process.